1926
DOI: 10.1113/jphysiol.1926.sp002271
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stimulation of the vagi on the pyloric region of the stomach

Abstract: THE course taken by the vagus fibres which supply the pyloric region has not been very definitely ascertained. Anatomically the main branches of the anterior and posterior vagal trunks from the cesophageal plexus are traceable to the region of the incisura angularis and their terminal fibres supply the pyloric antrum. In no instance does the anterior or posterior vagal trunk send fibres as far as the pylorus canal or sphincter. Many observers state, however, that all the pyloric region receives its nerve suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1927
1927
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Mixed effects on vagal stimulation were only seen at low frequencies and may have been due either to the inclusion of a few muscle fibres from the stomach or oesophagus (which are contracted by vagal stimulation) or to a mixture of adrenergic and cholinergic nerves in the vagus, as suggested by Paton and Vane (1956). Either interpretation would be in accord with the views of McCrea et al (1925), who found that the effect of vagal stimulation was dependent upon the resting tone of the sphincter. In a muscle with a low tonus, excitatory effects would show up best, but if the muscle is already contracted relaxation would predominate.…”
Section: Effects Of Vagotomy On Opening Pressures Withsupporting
confidence: 77%
See 2 more Smart Citations
“…Mixed effects on vagal stimulation were only seen at low frequencies and may have been due either to the inclusion of a few muscle fibres from the stomach or oesophagus (which are contracted by vagal stimulation) or to a mixture of adrenergic and cholinergic nerves in the vagus, as suggested by Paton and Vane (1956). Either interpretation would be in accord with the views of McCrea et al (1925), who found that the effect of vagal stimulation was dependent upon the resting tone of the sphincter. In a muscle with a low tonus, excitatory effects would show up best, but if the muscle is already contracted relaxation would predominate.…”
Section: Effects Of Vagotomy On Opening Pressures Withsupporting
confidence: 77%
“…The reactions of this last 2 cm. were also different from those of the body of the oesophagus and from those of the stomach, so that it cannot be said to behave as part of the gastric musculature as suggested by Carlson et al (1922) and by McCrea et al (1925). The region of the sphincter comprises a longitudinal and circular muscle coat with mucous membrane containing the finely distributed muscularis mucosa.…”
Section: Effects Of Vagotomy On Opening Pressures Withmentioning
confidence: 99%
See 1 more Smart Citation
“…On decreasing the pH a grouping of contractions was frequently observed in the region of pH 7.1. We have termed the condition "spasm " 150 owing to the similarity of the tracings to those obtained by Mc Crea and McSwiney (6). These observers in recording the movements of the pyloric antrum on stimulation of the peripheral end of the vagus nerve found that " a strong stimulus may cause a sustained contraction, the rhythmic movements increasing in rate and starting above the base line indicating summation."…”
Section: Discussionmentioning
confidence: 83%
“…Inhibition of movement of the pyloric antrum is independent of a rise of bloodpressure, and takes place when motor responses are observed in the body of the stomach. Moreover, McCrea and MacDonald [1928] point out that the inhibitory effect of adrenaline on the stomach is well shown in doses which produce a fall in blood-pressure, whereas the motor effect is most frequently obtained with large doses when there is a very great rise of blood-pressure. McCrea and McSwiney [1928] have shown that splanchnic stimulation can cause contraction of the stomach during compression of the thoracic aorta.…”
mentioning
confidence: 99%